Organização e ações de resistência dos atingidos no processo de implantação da Usina Hidrelétrica Baixo Iguaçu - PR e a criação do projeto de reassentamento - Carmo , Diego do (2022)
The implementation of large hydroelectric power stations has caused damage to many people directly or indirectly, who are those affected by the construction and its reservoir, resulting in a process of deterritorialization. This dissertation analyses the construction process of the Baixo Iguaçu Hydroelectric Power Station, henceforth H.P.S, and how was the territorial reconfiguration of those affected in the municipalities of Capitão Leônidas Marques and Capanema. It was sought as general objective: to analyze the action, resistance strategies and organization of the affected population – and deterritorialized – by Baixo Iguaçu H.P.S. and the claim to establish resettlement projects – reterritorialization – as social and economic compensation. To develop the research were accomplished readings to comprehend the conception of affected and territory. It was applied a semi-structured interview within a group of affected from the municipalities of Capitão Leônidas Marques and Capanema. Throughout this research it was possible to understand more about multiterritoriality and the context of the MAD (Movement of Affected by Dams) and the acts of resistance which helped the affected to receive a more forthright settlement in the construction of the Baixo Iguaçu Hydroelectric Power Station.